2021
DOI: 10.3390/diagnostics11060998
|View full text |Cite
|
Sign up to set email alerts
|

Large Bowel Ischemia/Infarction: How to Recognize It and Make Differential Diagnosis? A Review

Abstract: Ischemic colitis represents the most frequent form of intestinal ischemia occurring when there is an acute impairment or chronic reduction in the colonic blood supply, resulting in mucosal ulceration, inflammation, hemorrhage and ischemic necrosis of variable severity. The clinical presentation is variable and nonspecific, so it is often misdiagnosed. The most common etiology is hypoperfusion, almost always associated with generalized atherosclerotic disease. The severity ranges from localized and transient is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…Colonic ischemia is caused by markedly reduced blood supply leading to cellular metabolic dysfunction, colonic inflammation, ulceration or eventually necrosis [ 14 , 15 ]. Venous colonic ischemia is uncommon [ 15 , 16 ]. PC is a rare form of nonthrombotic venous colonic ischemia almost exclusively seen in individuals of Asian ancestry [ 1 – 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonic ischemia is caused by markedly reduced blood supply leading to cellular metabolic dysfunction, colonic inflammation, ulceration or eventually necrosis [ 14 , 15 ]. Venous colonic ischemia is uncommon [ 15 , 16 ]. PC is a rare form of nonthrombotic venous colonic ischemia almost exclusively seen in individuals of Asian ancestry [ 1 – 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As seen in our patients, PC could manifest a great variety of symptoms ranging from severe abdominal pain to asymptomatic and thus to obtain a diagnosis solely based on clinical findings seemed impossible in clinical practice. In addition to noninvasive diagnosis of PC by demonstration of characteristic curvilinear mesenteric venous calcifications [ 5 11 ], CT could offer colonic wall, pericolic and peritoneal details which were crucial for treatment decision, particularly for those presented with acute abdomen [ 15 , 16 ]. Our result showed that the AA-group exhibited a significantly thicker colonic wall (mean ± SD, 10.5 ± 3.4 mm), more involved segments and pericolic inflammation than the CP-group and CS-group on initial CT.…”
Section: Discussionmentioning
confidence: 99%
“…For pancreatic lesions, the contrast study protocol should include the delayed phase for the detection of delayed enhancement presented by some fibrous tumors. CT is an excellent method for detecting complications secondary to GEP-NETs, such as a bowel obstruction, intussusception, or desmoplastic reaction, which are life-threatening diseases [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. The right timing of the arterial phase is crucial for appropriate imaging.…”
Section: Diagnosis Staging and Risk Assessmentmentioning
confidence: 99%
“…Identifying the source of the bleeding can be difficult due to the wide range of potential causes, the length of the gastrointestinal tract and the intermittent nature of the bleeding [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The diagnostic and therapeutic approach is fully dependent on the nature of the bleeding and the patient’s haemodynamic status.…”
Section: Introductionmentioning
confidence: 99%